A novel Ag/BiOBr nanoplate catalyst with high photocatalytic activity in the decomposition of dyes - Yu, C.; Fan, C.; Meng, X.; Yang, K.; Cao, F.; Li, Xin Yong (2011)
A novel Ag/BiOBr composite catalyst has been synthesized by a solution combination with photodeposited method. The as-synthesized catalysts were characterized by powder X-ray diffraction, scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, and UV–Vis diffuse reflectance spectra. The photocatalytic reaction tests in the degradation of the dyes of acid orange II, rhodamine B and methyl orange showed that the deposition of optimal amount of 1–2 wt% Ag could bring about a big increase in the activity under visible light irradiation. The high photocatalytic performance could be attributed to the strong visible light absorption and low recombination rate of the e−/h+ pairs resulted in by the presence of metal silver nanoparticles.